2005
DOI: 10.1088/0268-1242/20/7/018
|View full text |Cite
|
Sign up to set email alerts
|

THz imaging and sensing for security applications—explosives, weapons and drugs

Abstract: Over the past 5 years, there has been a significant interest in employing terahertz (THz) technology, spectroscopy and imaging for security applications. There are three prime motivations for this interest: (a) THz radiation can detect concealed weapons since many non-metallic, non-polar materials are transparent to THz radiation; (b) target compounds such as explosives and illicit drugs have characteristic THz spectra that can be used to identify these compounds and (c) THz radiation poses no health risk for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
647
0
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,563 publications
(687 citation statements)
references
References 62 publications
5
647
0
7
Order By: Relevance
“…Such devices are required for weather radar applications, for tracking nano-satellites and space debris, as well as for plasma diagnostics, volcano monitoring, and quality control of pharmaceutical products, and for the study of historical artefacts. [1][2][3] In recent work, [4][5][6] it has been suggested that periodic patterns machined on the inner surface of a cylindrical conductor exhibit properties of a thin dielectric layer allowing such phenomena as Cherenkov instabilities to be observed. In particular this is an attractive possibility for creating high-intensity sources of THz radiation driven by mildly relativistic electron beams, as such structures should allow very effective heat, stress, and electric charge management via their quick dissipation into the main body "sink" of the material.…”
mentioning
confidence: 99%
“…Such devices are required for weather radar applications, for tracking nano-satellites and space debris, as well as for plasma diagnostics, volcano monitoring, and quality control of pharmaceutical products, and for the study of historical artefacts. [1][2][3] In recent work, [4][5][6] it has been suggested that periodic patterns machined on the inner surface of a cylindrical conductor exhibit properties of a thin dielectric layer allowing such phenomena as Cherenkov instabilities to be observed. In particular this is an attractive possibility for creating high-intensity sources of THz radiation driven by mildly relativistic electron beams, as such structures should allow very effective heat, stress, and electric charge management via their quick dissipation into the main body "sink" of the material.…”
mentioning
confidence: 99%
“…5 While much spectroscopic information can be obtained from pellet samples, in many cases their THz spectra exhibit broad line shapes due to intrinsic line broadening mechanisms, and to effects related to pellet preparation. 6 A promising method for investigating the THz properties of organic solids is through the use of THz waveguides. [7][8][9] For waveguide terahertz timedomain spectroscopy ͑THz-TDS͒ the parallel plate metal waveguide ͑PPWG͒ is particularly useful because of the nondispersive and low loss propagation for the transverse electromagnetic mode.…”
mentioning
confidence: 99%
“…Such laser source emitting tunable THz radiation is of great interest for a number of applications, including indoor communications [27,28], biomedical imaging [29,30], spectroscopy [31,32], homeland security and defense [33,34], among others.…”
Section: Discussionmentioning
confidence: 99%